Strategies and challenges faced by professionals of radiological techniques in the health care of deaf patients (Research, Society and Development, 2021)
The access to services essential to life by the deaf community is a great challenge in their lives, due to the communication difficulties found in these environments. The health service is one of the main ones, as it is a service that communication is essential for the success of the service. Because of this, the objective of the research is to know how communication between deaf patients and the professional of radiological techniques takes place during imaging exams and radiological therapies. From this, a descriptive study with a quantitative approach was carried out, involving 82 professionals of radiological techniques, who were interviewed between 05/18/2021 to 05/28/2021 by the Google Forms platform, in accordance with the precepts of Resolution 466/ 12. The professionals interviewed are over 18 years old and had already provided healthcare to deaf patients during their profession. The results obtained showed that communication between this professional and deaf patient is really a communicative barrier, but that it is overcome through the use of space-visual communication strategies, and that most professionals in radiology techniques believe in the need for training in Libras, in order to offer better service. Finally, it is possible to conclude that from the use of several methods as well as the assistance of the companion, most imaging tests/radiological therapies were successfully performed. However, this result does not exclude the need for training in Libras, which is essential for better efficiency in caring for the deaf.